The truffle hunters [videorecording (DVD)] - Botto, Piero; Cicciu, Maria; Cauda, Sergio (Sony Pictures Home Entertainment, 2021)
A handful of men and their expertly trained dogs search for rare, expensive and delicious white Alba truffles deep in the forests of Piedmont, Italy.